2022
DOI: 10.3389/fendo.2022.867965
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly Caused by Ectopic Growth Hormone Releasing Hormone Secretion: A Review

Abstract: IntroductionEctopic acromegaly is a rare condition caused most frequently by growth hormone releasing hormone (GHRH) secretion from neuroendocrine tumors. The diagnosis is often difficult to establish as its main symptoms do not differ from those of acromegaly of pituitary origin.ObjectivesTo determine most common clinical features and diagnostic challenges in ectopic acromegaly.Patients and MethodsA search for ectopic acromegaly cases available in literature was performed using PubMed, Cochrane, and MEDline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 102 publications
0
5
0
10
Order By: Relevance
“…Только в двух случаях ГРРГ-продуцирующие опухоли имели не нейроэндокринную природу (диффузная крупная В-клеточная лимфома [ 15 ] и аденокистозная карцинома легкого [ 16 ]). Среди интракраниальных источников эктопической продукции ГРРГ чаще встречаются смешанные ганглиоцитомы-аденомы гипофиза [ 14 ].…”
Section: актуальностьunclassified
See 2 more Smart Citations
“…Только в двух случаях ГРРГ-продуцирующие опухоли имели не нейроэндокринную природу (диффузная крупная В-клеточная лимфома [ 15 ] и аденокистозная карцинома легкого [ 16 ]). Среди интракраниальных источников эктопической продукции ГРРГ чаще встречаются смешанные ганглиоцитомы-аденомы гипофиза [ 14 ].…”
Section: актуальностьunclassified
“…Клиническая картина эктопической акромегалии не отличается от таковой при типичной акромегалии, а заподозрить ее можно при отсутствии визуализации аденомы гипофиза по данным магнитно-резонансной томографии (МРТ) головного мозга или при выявлении диффузной гиперплазии гипофиза [ 17 ]. Сложность диагностики эктопической акромегалии заключается в поиске источника продукции ГРРГ, а основным методом лечения является удаление первичной опухоли [ 13 ][ 14 ]. В случае невозможности радикального удаления опухоли могут быть назначены аналоги соматостатина длительного действия, пэгвисомант, химиотерапия, иммунотерапия, лучевая терапия [ 13 ][ 14 ].…”
Section: актуальностьunclassified
See 1 more Smart Citation
“…Acromegaly due to ectopic GHRH secretion, similarly to acromegaly caused by a GH‐secreting pituitary tumour, responds favourably to SSA, 104,105 making them the first‐line choice [3, B]. In cases of continued IGF‐1 elevation, pegvisomant can be added to control the acromegaly effects [4, D].…”
Section: Introductionmentioning
confidence: 99%
“…When combined, two series have shown that PRRT led to improvement of VIPoma symptoms in nine out of 11 patients 92,103. Together, these limited retrospective data make chemotherapy, sunitinib and PRRT second-line options to be considered in patients with refractory advanced VIPoma, especially in cases of disease progression[4, D].Acromegaly due to ectopic GHRH secretion, similarly to acromegaly caused by a GH-secreting pituitary tumour, responds favourably to SSA,104,105 making them the first-line choice[3, B]. In cases of continued IGF-1 elevation, pegvisomant can be added to control the acromegaly effects[4, D].…”
mentioning
confidence: 99%